2003
DOI: 10.1146/annurev.neuro.26.041002.131022
|View full text |Cite
|
Sign up to set email alerts
|

PAIN MECHANISMS: Labeled Lines Versus Convergence in Central Processing

Abstract: The issue of whether pain is represented by specific neural elements or by patterned activity within a convergent somatosensory subsystem has been debated for over a century. The gate control theory introduced in 1965 denied central specificity, and since then most authors have endorsed convergent wide-dynamic-range neurons. Recent functional and anatomical findings provide compelling support for a new perspective that views pain in humans as a homeostatic emotion that integrates both specific labeled lines an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

22
482
6
9

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 678 publications
(519 citation statements)
references
References 117 publications
22
482
6
9
Order By: Relevance
“…The anterior insula, in particular, has been previously associated with anticipatory responses to painful stimuli (Craig, 2003;Koyama et al, 2005;Ploghaus et al, 1999;Tracey, 2005). Although this region was identified by its monotonically increasing response to expected magnitude, it also showed a significantly nonlinear NPRR (Fig.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The anterior insula, in particular, has been previously associated with anticipatory responses to painful stimuli (Craig, 2003;Koyama et al, 2005;Ploghaus et al, 1999;Tracey, 2005). Although this region was identified by its monotonically increasing response to expected magnitude, it also showed a significantly nonlinear NPRR (Fig.…”
Section: Discussionmentioning
confidence: 94%
“…Moreover, no comparable data exist in monkeys using aversive paradigms. The ACC is an integral component of the cortical pain matrix, and current evidence suggests that the ACC integrates several dimensions of the subjective pain experience, including emotional and attentional components (Craig, 2003;Ploghaus et al, 1999;Vogt, 2005). Interestingly, studies of positive financial incentives have also shown a significant interaction of probability and magnitude in the ACC (Knutson et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…This would also account for a willingness to bring adverse outcomes forward in time, if possible. In the experiment described here, these two explanations imply a different time course of activation in the pain matrix, a network of brain regions associated with unpleasant or noxious stimuli (Ploghaus et al, 1999;Koyama, McHaffie, Laurienti, & Coghill, 2005;Rajj et al, 2005;Tracy, 2001;Craig, 2003;Peyron et al, 2000). Measuring the time profile of activation allows us to distinguish between the two explanations.…”
Section: Why Do People Want To Get An Adverse Experience Over With Asmentioning
confidence: 91%
“…Both SI and SII have generally been associated with the physical intensity of noxious stimulation (Tracy, 1999;Craig, 2003;Petrovic, Petersson, Hansson, & Ingvar, 2002;Bentley et al, 2004), whereas the caudal ACC has been associated with the attentive component of pain (Vogt, 2005;Bentley, Derbyshire, Youell, & Jones, 2003). The localization of dread to the posterior elements of the matrix suggests that dread has a substantial attentive component.…”
Section: Why Do People Want To Get An Adverse Experience Over With Asmentioning
confidence: 99%
See 1 more Smart Citation